Моби Дик, или Белый Кит: роман / Герман Мелвилл - Мелвилл Герман (Азбука-классика, 2007)
Экземпляры: (20220413) / Инвентарный номер: 32959 / Цена: 85.80 / Сис.шифр: 84(7Сое) / Авт.знак: М 47 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)